2000
DOI: 10.1046/j.1365-2125.2000.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic‐pharmacodynamic evaluation of ceftazidime continuous infusion vs intermittent bolus injection in septicaemic melioidosis

Abstract: Aims  Experimental studies have suggested that constant intravenous infusion would be preferable to conventional intermittent bolus administration of beta‐lactam antibiotics for serious Gram‐negative infections. Severe melioidosis (Burkholderia pseudomallei infection) carries a mortality of 40% despite treatment with high dose ceftazidime. The aim of this study was to measure the pharmacokinetic and pharmacodynamic effects of continuous infusion of ceftazidime vs intermittent bolus dosing in septicaemic melioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…In that study a bolus dose of 12 mg/kg intravenously followed by a constant infusion of 4 mg/kg/h was found to provide an adequate dose while allowing for a total lower dose to be delivered than with traditional 8-h bolus dosing (7). These data support the use of elastomeric infusion devices (Baxter, Sydney, Australia) through a peripherally inserted central catheter to complete intensive-phase antibiotic therapy for melioidosis in Australia (111,206).…”
Section: Antibiotic Treatmentsupporting
confidence: 48%
“…In that study a bolus dose of 12 mg/kg intravenously followed by a constant infusion of 4 mg/kg/h was found to provide an adequate dose while allowing for a total lower dose to be delivered than with traditional 8-h bolus dosing (7). These data support the use of elastomeric infusion devices (Baxter, Sydney, Australia) through a peripherally inserted central catheter to complete intensive-phase antibiotic therapy for melioidosis in Australia (111,206).…”
Section: Antibiotic Treatmentsupporting
confidence: 48%
“…Accordingly, several clinical trials have been initiated over the last half-decade, most notably in difficult-to-treat situations such as suspected gram-negative infections in critically ill patients (3), severe infections in intensive care patients (8,16,21,24,37), septicemia (1), severe sepsis (20), and cystic fibrosis (29,40). Yet, as clearly pointed out by one of the first promoters of the continuous infusion of ␤-lactams (6), this mode of administration, through programmable pumps or other similar devices, requires the drug to remain sufficiently stable in solution over the projected duration of the infusion.…”
mentioning
confidence: 99%
“…Thus, it has been suggested that maintaining concentrations above the MIC for 90-100% of the dosing interval is an appropriate PD target for critically ill patients and may prevent antibiotic resistance [5,148,149]. It has also been demonstrated that maximal bactericidal activity occurs when drug concentrations are maintained at four-to five-times the MIC, with higher concentrations providing little added benefit [23,25,26,147,[150][151][152]. Thus, it has been suggested that beta-lactam concentrations should be maintained at least four-to five-times the MIC for extended periods during each dosing interval [5,7,153].…”
Section: Beta-lactam Antibiotics and Their Pharmacokinetic And Pharmamentioning
confidence: 99%
“…Research has shown that improved antibiotic exposure can be obtained via three general approaches: (1) increasing the antibiotic dose; (2) increasing the frequency of antibiotic dosing or; (3) by utilizing EI or CI [67,85,86,106,151,[164][165][166][167][168][169][170][171][172][173][174][175]. However, increasing the antibiotic dose has been shown to be less effective to adequately maintain effective drug concentration during a dosing period.…”
Section: Beta-lactam Antibiotics and Their Pharmacokinetic And Pharmamentioning
confidence: 99%
See 1 more Smart Citation